Alain e a arquitetura: uma contribuição para a história das relações entre arte e arquitetura - Vânia Myrrha de Paula e Silva (2011)
The objective of this dissertation is to contribute to the history of the relations between different types of arts, in the beginning of the twentieth century, emphasizing the view of the relations between architecture and arts studied by Émile-Auguste Chartier (1868-1951), a French philosopher and professor writing under the pseudonym of Alain. Texts on architecture, painting, sculpture and drawing found in two of his books, Système des Beaux Arts (1920) e Vingt leçons sur les Beaux-Arts (1931) will be used. This analysis will lead to a better knowledge of part of Alainøs work and his thoughts on the relation between Architecture and the arts; how he relates them and how the system proposed by him works, as well as to foster interlocution among them.